PENGARUH DOSIS EKSTRAK ETANOL DAUN KAYU JAWA (Lannea coromandelic (Houtt.) Merr.) TERHADAP AKTIVITAS ANTIINFLAMASI PADA TIKUS (Rattus norvegicus). - Putra, Bayu; Rahman, Safriani (Fakultas Farmasi UMI, 2019)
In general, anti-inflammatory drugs that currently available have great side effects. One of plant that suspected have anti-inflammatory effect is Kayu Jawa (Lannea coromandelic (Houtt). Merr). Objective of this research is to determine anti-inflammatory effect and effective concentration from extract ethanol Kayu Jawa leaves. First treatment was start with rats group divided into 5 groups that initial foot volume have been measured, then 0.3 mL of 1% lambda carrageenan solution injected to rat’s left foot as inducer, then foot volume measured again. Furthermore, rat groups were given oral induction, 1st group were given NaCMC as control group, 2nd group were given Diclofenac Sodium as drugs control group, then 3rd, 4th, and 5th as test group were given ethanol extract of Kayu Jawa leaves 75 mg/kgBW, 150 mg/kgBW, and 300 mg/kgBW. Foot volume measured again using plestimometer every 1 hour for 5 hours. The result showed that with 75 mg/kgBW, 150 mg/kgBW dan 300 mg/kgBW of ethanol extract Kayu Jawa leaves have ability to reduce rat’s foots volume that induce with carrageenan. Ethanol extract of Kayu Jawa leaves with dosage 300 mg/kgBW have bigger percentage of reducing rat’s foots volume (56.30%) than the other groups.